2011
DOI: 10.1007/s00572-011-0405-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of arbuscular mycorrhizal symbiosis in root mineral uptake under CaCO3 stress

Abstract: This study investigated the effects of increasing CaCO(3) concentrations (0, 5, 10, 20 mM) on arbuscular mycorrhizal (AM) symbiosis establishment as well as on chicory root growth and mineral nutrient uptake in a monoxenic system. Although CaCO(3) treatments significantly decreased root growth and altered the symbiosis-related development steps of the AM fungus Rhizophagus irregularis (germination, germination hypha elongation, root colonization rate, extraradical hyphal development, sporulation), the fungus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 58 publications
(53 reference statements)
0
10
1
Order By: Relevance
“…Based on studies elsewhere, however, it is possible that the dry season constrains the AMF community to taxa that are physically or physiologically tolerant of low soil moisture (e.g., Glomus and Diversispora ; Augé, 2001 ) or to high soil P fertility or pH ( Wang et al, 2016 ). Alternatively, these shifts may reflect differences in host plant requirements during the dry season for AMF that increase host drought tolerance (e.g., stomatal control, cytokinin production; Augé, 2001 ) or increase the acquisition of limiting nutrients from carbonate substrates (N, Fe, Zn; Labidi et al, 2012 ). Irrespective, our results indicate a high potential to use our AMF protocol in large-scale sequencing projects to address AMF diversity with sufficient taxonomic precision, to determine the extent to which AMF assemblages vary across host plants and ecosystems, and to resolve AMF species’ responses to edaphic stressors, such as anthropogenic N deposition, in complex environmental samples.…”
Section: Discussionmentioning
confidence: 99%
“…Based on studies elsewhere, however, it is possible that the dry season constrains the AMF community to taxa that are physically or physiologically tolerant of low soil moisture (e.g., Glomus and Diversispora ; Augé, 2001 ) or to high soil P fertility or pH ( Wang et al, 2016 ). Alternatively, these shifts may reflect differences in host plant requirements during the dry season for AMF that increase host drought tolerance (e.g., stomatal control, cytokinin production; Augé, 2001 ) or increase the acquisition of limiting nutrients from carbonate substrates (N, Fe, Zn; Labidi et al, 2012 ). Irrespective, our results indicate a high potential to use our AMF protocol in large-scale sequencing projects to address AMF diversity with sufficient taxonomic precision, to determine the extent to which AMF assemblages vary across host plants and ecosystems, and to resolve AMF species’ responses to edaphic stressors, such as anthropogenic N deposition, in complex environmental samples.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in contrast with those showed by Garcia and Zimmermann [37] who concluded that plant K+ nutrition is clearly improved by mycorrhization. Moreover, Labidi et al [38] found that mycorrhization increased mineral nutrient uptake of chicory. Likewise, Ingraffia et al [39] compared nutrients uptake of wheat with and…”
Section: Correlation Between Mycorrhization Rate and Mineral Contentsmentioning
confidence: 99%
“…An important factor that contributes to regional endemic diversity is the adaptation of plants to unusual soils, such as calcareous soils (Aguirre-Liguori et al 2014). It has been shown that in calcareous soils P deficiency is frequent, since the presence of calcium carbonate (CaCO 3 ) decreases the solubility of this element, affecting its availability and therefore the yield of plants; deficiencies of iron (Fe), manganese (Mn) and zinc (Zn) have also been observed in calcareous soils (Labidi et al 2012). Our results showed that the soils of S 1 , S 2 , and S 3 are nutrient-deficient.…”
Section: Discussionmentioning
confidence: 99%